In vivo IL-10 gene delivery attenuates bleomycin induced pulmonary fibrosis by inhibiting the production and activation of TGF-β in the lung. Issue 10 (29th June 2006) - Nakagome, K; Dohi, M; Okunishi, K; Tanaka, R; Miyazaki, J; Yamamoto, K
Abstract : Backgroud: Idiopathic pulmonary fibrosis is a devastating disorder for which there is no effective treatment. Transforming growth factor (TGF)-β plays a critical role in provoking fibrosis. Interleukin (IL)-10 is a potent immunosuppressive cytokine but its effect on the fibrosing process is unclear. A study was undertaken to examine whether IL-10 affects the production and activation of TGF-β and thus can attenuate the fibrosis. Methods: Mice were given an intratracheal injection of bleomycin. On day 1 or 14, IL-10 gene was delivered by rapid intravenous injection of Ringer's solution containing plasmid. Two weeks after the plasmid injection the mice were examined for fibrosis. The effect of IL-10 on TGF-β production by alveolar macrophages was assessed. Results: Even when delivered during the fibrosing phase, IL-10 gene significantly suppressed the pathological findings, hydroxyproline content, and production of both active and total forms of TGF-β1 in the lung. Immunohistochemical analyses showed that alveolar macrophages were one of the major sources of TGF-β1 and IL-10 diminished the intensity of the staining. IL-10 also suppressed the expression of αV β6 integrin, a molecule that plays an important role in TGF-β activation, on lung epithelial cells. Alveolar macrophages from bleomycin injected mice produced TGF-β1 spontaneously ex vivo, which was significantly suppressed by treatment of the mice in vivo or by treatment of the explanted macrophages ex vivo with IL-10. Conclusion: IL-10 suppresses the production and activation of TGF-β in the lung and thus attenuates pulmonary fibrosis, even when delivered in the chronic phase.